2008
DOI: 10.1179/136485908x337508
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, comparative study of supervised and unsupervised artesunate–amodiaquine, for the treatment of uncomplicated malaria in Ghana

Abstract: Although the use of artesunate-amodiaquine treatment is growing in Africa, data on its effectiveness are limited. In only the second published comparison of supervised and unsupervised treatments with this combination, Ghanaian children with uncomplicated malaria have recently been investigated in an open-label, randomized, comparative study. Children aged 6-120 months attending the Navrongo War Memorial hospital between November 2005 and December 2006 were enrolled if they had uncomplicated Plasmodium falcipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In these children, there was an initial drop in haemoglobin followed by an increase by day 14 [20]. A similar pattern of haematological recovery post malaria treatment has been reported among other children in northern Ghana [18] and Kenyan children [21]. In this study, haemoglobin levels were determined only on days 0 and 2.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In these children, there was an initial drop in haemoglobin followed by an increase by day 14 [20]. A similar pattern of haematological recovery post malaria treatment has been reported among other children in northern Ghana [18] and Kenyan children [21]. In this study, haemoglobin levels were determined only on days 0 and 2.…”
Section: Discussionsupporting
confidence: 77%
“…Body weakness was commonly reported within the first two days posttreatment. Generally, the reported symptoms among this cohort of adults are less than that reported among children who were treated with AS+AQ in northern Ghana [18]. Compliance among participants in both supervised and unsupervised groups was high irrespective of side-effects they experienced during treatment phase.…”
Section: Discussionmentioning
confidence: 96%
“…Supervised dosing does ensure good treatment adherence, but it places a logistic and financial burden on health care providers, policy makers, and the patients, especially in rural areas where heath care access is difficult. This limits the implementation of IPT on a wider scale and might prevent an efficacious protection against new malaria infections (14). It is possible that adherence could be increased with simplified dosing regimens such as weekly dosing (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in infants and young children less than 30 months participating in a sulphadoxine-pyrimethamine/Placebo Intermittent Preventive Treatment (IPTi) trial who developed uncomplicated malaria and were treated with supervised or unsupervised AS/AQ [Oyakhirome et al, 2007], a significant difference in the risk of treatment failure between the two regimens in favor of the supervised treatment was reported. Similarly, in a comparison of supervised versus unsupervised AS/AQ in children 5 years or younger [Oduro et al, 2008], children treated with supervised AS/AQ were more likely to show an adequate clinical and parasitological response than children treated unsupervised.…”
Section: Efficacy and Effectiveness Of As/aqmentioning
confidence: 95%
“…The AS/AQ combination is more efficacious than amodiaquine monotherapy, and clinical trials from various countries, mainly in children, have reported high PCR-corrected, day-28 cure rates (Table 2) [Adjei et al, 2008b;Bonnet et al, 2007;Faucher et al, 2009;Faye et al, 2007;Grandesso et al, 2006;Guthmann et al, 2006;Kayentao et al, 2009;Kobbe et al, 2008;Koram et al, 2008;Martensson et al, 2005;Mutabingwa et al, 2005;Ndiaye et al, 2009;Oduro et al, 2008;Osorio et al, 2007;Owusu-Agyei et al, 2008;Oyakhirome et al, 2007;Sirima et al, 2009;Swarthout et al, 2006;Thanh et al, 2009;van den Broek et al, 2006]. However, comparative studies of the AS/AQ combination with other ACT regimens such as artemether-lumefantrine [Bukirwa et al, 2006;Martensson et al, 2005;Mutabingwa et al, 2005;van den Broek et al, 2006], or dihydroartemisinin-piperaquine [Hasugian et al, 2007], have shown a tendency towards a higher risk of recurrent parasitaemia after AS/AQ treatment, despite the high day-28 cure rates.…”
Section: Efficacy and Effectiveness Of As/aqmentioning
confidence: 99%